1987
DOI: 10.1126/science.3810155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrinsic Binding Energy from a Hydrogen Bonding Group in an Enzyme Inhibitor

Abstract: This and two accompanying reports describe the intrinsic binding energy derived from a single hydrogen bond between an inhibitor and an enzyme. The results were obtained by comparing matched pairs of inhibitors of the zinc endopeptidase thermolysin that bind to the enzyme in an essentially identical manner but differ in the presence or absence of a specific hydrogen bond. This report describes five phosphorus-containing analogs of the peptides carbobenzoxy-Gly-Leu-X, in which the Gly-Leu peptide linkage is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
3
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(83 citation statements)
references
References 17 publications
3
75
3
2
Order By: Relevance
“…It should be noted that these relations are only applicable for inhibitors with minimal size modifications such as Based on Equation 2 and our FDPB results in Table 2, we esZGp(0)LL and ZGP(C)LL, respectively. If AGindirect's are small, our results agree with Bartlett and Marlowe's (1987) estimate that AGH.bond(I)'S are significantly higher than the observed A G, 's.…”
Section: + E (~' 3 )supporting
confidence: 81%
See 2 more Smart Citations
“…It should be noted that these relations are only applicable for inhibitors with minimal size modifications such as Based on Equation 2 and our FDPB results in Table 2, we esZGp(0)LL and ZGP(C)LL, respectively. If AGindirect's are small, our results agree with Bartlett and Marlowe's (1987) estimate that AGH.bond(I)'S are significantly higher than the observed A G, 's.…”
Section: + E (~' 3 )supporting
confidence: 81%
“…The more hydrophilic nature of phosphonamidates is also confirmed in a recent FDPB calculation of CH,-PO,-X-CH,, in addition to early FEP calculations of the inhibitors. Bartlett and Marlowe (1987) and Morgan et al (1991) analyzed the binding mechanism of these inhibitors using Scheme I (Fig. 2).…”
Section: Solvationmentioning
confidence: 99%
See 1 more Smart Citation
“…• C), compared to fully-hydrogen-bonded ligands (133,134). In the second position, the density observed for the U·G base pair was most consistent with Watson-Crick rather than wobble geometry (Figure 2e).…”
mentioning
confidence: 54%
“…Several studies using thermolysin indicated that phosphonamidate analogues of the peptides bound >800 times stronger than the corresponding phosphonate analogue, due to the fact that the phosphonamidate could form one additional H-bond to the enzyme. 11,12 To probe whether the phosphonamidate analogue of dAla-d-Ala had a similar increase in binding anity to…”
mentioning
confidence: 99%